1-2x=x/3-x/2= ajudar aí !!!!!!!!!!!!!
claudiagsantos21:
Alguém um pouco mais rápido
Soluções para a tarefa
Respondido por
1
Resolução:
1 - 2x = x / 3 - x / 2
mmc = 6
6 / 6 - 12x / 6 = 2x / 6 - 3x / 2
6 - 12x = 2x - 3x
- 12x - 2x + 3x = - 6
- 14x + 3x = - 6
- 11x = - 6 * (-1)
11x = 6
x = 6 / 11
1 - 2x = x / 3 - x / 2
mmc = 6
6 / 6 - 12x / 6 = 2x / 6 - 3x / 2
6 - 12x = 2x - 3x
- 12x - 2x + 3x = - 6
- 14x + 3x = - 6
- 11x = - 6 * (-1)
11x = 6
x = 6 / 11
Perguntas interessantes
Matemática,
10 meses atrás
Filosofia,
10 meses atrás
História,
10 meses atrás
Física,
1 ano atrás
Português,
1 ano atrás
Ed. Física,
1 ano atrás